2019
DOI: 10.1016/j.physletb.2019.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological comoving behavior of the configurational entropy

Abstract: It has been shown that a functional dependence of the configurational entropy (CE) density exhibits a cosmological comoving behavior related to the scale parameter, a, of the FRW flat universe. Such a circumstantial comoving behavior shows that the CE evolves with a −3 for fermionic and bosonic radiation and with a −3/2 for non-relativistic fermionic matter. The results are discussed in the domain of matter and radiation, as well as in a simplified context of the ΛCDM cosmology. Our results suggest that the CE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Such a behavior was observed in many different physical systems, such as: compact astrophysical objects [4] and holographic AdS/QCD models [5][6][7][8][9][10]. There are other many interesting applications of configuration entropy in the literature, as for example [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The purpose of the present letter is to investigate the application of the configuration entropy to a physical system of great interest currently: heavy mesons inside a quark gluon plasma with finite density. The insterest in such a system comes from the quark gluon plasma (QGP).…”
Section: Introductionmentioning
confidence: 87%
“…Such a behavior was observed in many different physical systems, such as: compact astrophysical objects [4] and holographic AdS/QCD models [5][6][7][8][9][10]. There are other many interesting applications of configuration entropy in the literature, as for example [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The purpose of the present letter is to investigate the application of the configuration entropy to a physical system of great interest currently: heavy mesons inside a quark gluon plasma with finite density. The insterest in such a system comes from the quark gluon plasma (QGP).…”
Section: Introductionmentioning
confidence: 87%
“…We also added a longevity study of two-dimensional oscillons, since these too have yet to be shown to decay in numerical simulations. Motivated by these results, in the present work we extend our studies of the longevity of resonant and 2d oscillons using a recently proposed measure of spatial complexity known as Configurational Entropy (CE) [32], which has been applied to many physical systems, from solitons in field theories [33][34][35][36][37][38] to phase transitions [39][40][41], and to astrophysics and cosmology [42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The above result has been discussed, for instance, in phase-space quantum cosmological scenarios in order to reproduce the classical cosmological background from a quantum approach [11] and can be relevant in more general contexts involving the discussion of the informational content of cosmological scenarios [25]. By substituting the expression from Eq.…”
Section: Computation Of Purity -An Example Of Pure Statementioning
confidence: 99%